2014
DOI: 10.1021/jo500044d
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Physical Organic Chemistry

Abstract: A perspective on the development of mechanistic carbene chemistry is presented. The author will point out questions that have been answered, and a next generation of questions will be proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 70 publications
(174 reference statements)
0
31
0
Order By: Relevance
“…The combination of ultrafast transient vibrational absorption spectroscopy (TVAS) and TEAS is powerful for investigation of bimolecular radical-reaction mechanisms because the formation and decay of the initial radical can be monitored by TEAS, with subsequent reaction intermediates observed by TVAS. [19][20][21] Here, we demonstrate that TVAS at discrete time delays from 200 fs to 50 s in a single set of measurements, combined with TEAS over a more restricted time range from 100 fs -1.3 ns, provides a comprehensive view of a sequence of unimolecular initiation and bimolecular addition steps in a radical chain reaction.…”
Section: Introductionmentioning
confidence: 71%
“…The combination of ultrafast transient vibrational absorption spectroscopy (TVAS) and TEAS is powerful for investigation of bimolecular radical-reaction mechanisms because the formation and decay of the initial radical can be monitored by TEAS, with subsequent reaction intermediates observed by TVAS. [19][20][21] Here, we demonstrate that TVAS at discrete time delays from 200 fs to 50 s in a single set of measurements, combined with TEAS over a more restricted time range from 100 fs -1.3 ns, provides a comprehensive view of a sequence of unimolecular initiation and bimolecular addition steps in a radical chain reaction.…”
Section: Introductionmentioning
confidence: 71%
“…Importantly, these intermolecular interactions can modulate the lifetime, intersystem crossing, and reactivity rates of carbenes. 1921 It has frequently been observed that polar solvents selectively stabilize the singlet state. 14,17 In the case of triplet ground-state carbenes, complexation with highly polar compounds can render the singlet state sufficiently accessible to participate in a reaction, or may even invert the singlet–triplet gap ( E S–T ), resulting in a singlet ground state.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 They yield carbenes photochemically under mild conditions. 19,20 Ultrafast time-resolved laser flash photolysis of aryl diazo compounds [21][22][23] and aryldiazirines [24][25][26] has provided valuable information on the dynamics of the precursor excited states and the generated singlet arylcarbenes. Using ultrafast infrared spectroscopy, the singlet aryldiazomethane and arylcarbene intermediates were detected in the photolysis of phenyldiazirine, phenylchlorodiazirine and p-methoxy-3-phenyl-3-methyldiazirine in less than 1 ps upon excitation.…”
Section: Introductionmentioning
confidence: 99%